Cutting Corners: Provider Perceptions of Interpretation Services and Factors Related to Use of an Ad Hoc Interpreter. (June 2016) - Mayo, Rachel; Parker, Veronica G.; Sherrill, Windsor W.; Coltman, Kinneil; Hudson, Matthew F.; Nichols, Christina M.; Yates, Adam M.; Pribonic, Anne Paige
Introduction: This study assessed health providers' perceptions of factors related to professional interpretation services and the association between these factors and the potential use of ad hoc interpreters. Method: Data were collected from a convenience sample of 150 health services providers at a large, regional health system in South Carolina. Results: Providers rated "ability to communicate effectively during a clinical encounter" as paramount regarding the use of interpretation services. The most important factors related to the likely use of ad hoc interpreters (cutting corners) included locating a qualified interpreter, having to wait for a qualified interpreter, and technical difficulties regarding phone and video technology. Conclusion: Health care organizations may benefit from increasing staff awareness about patient safety and legal and regulatory risks involved with the use of ad hoc interpreters.